Food Storage on the Appalachian Trail: A Theory of Planned Behavior Approach to Understanding Backpacker Bear Canister Use. Issue 2 (November 2021) - Freeman, Stephanie; Lawhon, Ben; Newman, Peter; Derrick Taff, Brendan
Improper food storage fuels human-bear conflicts in parks and protected areas around the globe. Bear-resistant food storage canisters provide an extremely effective solution for reducing food-related human-bear conflicts, especially for overnight visitors in backcountry settings. However, the success of this intervention depends on recreationists' willingness to use and comply with such food storage methods. This study used internet-based surveys to identify Appalachian Trail backpackers' attitudes, norms, perceived behavioral control, and intentions regarding the use of bear canisters through an application of the Theory of Planned Behavior. Results indicate attitudes and subjective norms provide potential leverage points for messaging under voluntary conditions; messaging incorporating attitudes, subjective norms, and perceived behavioral control may help influence food storage behavior under required conditions. Specific recommendations for effective, theory-based interpretation strategies aimed at reducing human-black bear conflicts on the Appalachian Trail are provided.